Thermoelectric MgAgSb alloys for sustainable energy application. (25th August 2022) - Iqbal, Younas; Wang, Jianli; Wang, Chao; Muhammad, Pir; Zada, Amir; Khan, Maaz; Maab, Husnul; Khan, Qasim; Maqbool, Muhammad
Summary: Solid‐state thermoelectric (TE) devices are known for converting solar energy and waste heat into electricity, which provides a substitute path for energy production and utilization to commence the challenges of energy sustainability. To develop TE devices, it is important to identify thermoelectrically active materials with the potential converting solar energy and heat into electrical energy. In ambient settings, TE devices are one of the most pollution‐free methods of energy conversion since it is noiseless, essentially maintenance‐free, and able to provide electricity continuously for several years. A surge in interest in TE harvesting for diverse uses, including extracting waste heat from automobile exhaust and industrial processes has occurred in recent years. For an efficient TE device, a number of variables must be addressed. These include the availability of TE materials with high ZT, construction of ohmic connections between thermoelements and metallic interconnect, material engineering and defects systems, and the control of maximum heat transport through the device. The current review summarized a recent understanding of a reliable and eco‐friendly strategy for synthesizing pure MgAgSb alloy and its TE performance enhancement. First, a discussion on the various strategies employed to improve ZT and band structure determination is described. Then, we provided an overview of excellent TE performance, applications of bandgap engineering to enhance TE ZT value and their capacity to produce energy, and good quality nanostructured a‐MgAgSb to produce long‐term, thermally stable microstructure. Finally, we will look at how well a single‐leg device converts power. The current mysteries, along with future perspectives and challenges for this material system, are described in the outlook section. Abstract : MgAgSb is a promising thermoelectric (TE) material to generate sustainable TE energy. TE figure‐of‐merit (ZT) enhances the TE performance, which requires a good synthesis technique. Critical analyses of those high‐performance TE materials are also performed which need good bipolar effects for excellent TE performance, bandgap engineering to enhance TE figure‐of‐merit value, and good quality nanostructured α‐MgAgSb to produce long‐term, environmentally stable microstructures.